Afatinib (BIBW-2992): a novel dual EGFR/HER2neu inhibitor with promising activity in non-small-cell lung cancer. Issue 1 (January 2011) - Bordoni, Rodolfo E
Lung cancer is not one disease but many diseases with specific molecular profiles and treatment alternatives. EGF receptor-activating mutations predict a high, albeit short-lived, response to reversible tyrosine kinase inhibitors (e.g., gefitinib and erlotinib). Acquired resistance mutations can result in tumor progression. Dual EGFR/HER2 irreversible inhibitors are small novel molecules that can overcome gefitinib/erlotinib resistance by potentially circumventing multiple mechanisms of acquired resistance, as shown in vitro . Afatinib is an irreversible inhibitor with potent phosphorylation inhibitory activity of both EGF receptor and HER2. Durable responses were observed in Phase I trials in advanced non-small-cell lung cancer at 50 mg once daily. In Phase II trials, reduction in tumor size was observed in 90% of patients. The objective response and disease control rate were 62 and 94%, respectively. Median progression-free survival was estimated at 12 months (95% CI: 10.0–19.2). The most common drug-related adverse events were diarrhea and rash/acne, 18% were grade 3 and none grade 4. LUX-Lung 1, one of two global Phase III studies, was presented in October 2010. At primary analysis (358 events), the study did not meet its primary end point to improve overall survival compared with placebo.